Global risk of cardiovascular disease. (1st May 2003) - Poulter, N
Abstract : UK death rates from coronary heart disease are among the highest in the world. This is because the UK has high levels of standard risk factors and a low level of intervention on those risk factors. The most important modifiable cardiovascular risk factors are dyslipidaemia (particularly high LDL cholesterol and low HDL cholesterol), smoking, hypertension, glucose intolerance, and central obesity. Intervention strategies that do not target those individuals at highest cardiovascular risk are likely to be less cost effective. Global risk estimation is increasingly recognised by management guidelines as a clinically and cost effective means of guiding treatment. However, an over reliance on short term absolute risk may result in under treatment of young people (particularly women) at high relative risk and over treatment of older people (particularly men) at low relative risk.